2015
DOI: 10.1002/jbmr.2507
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Induced Effects on Osteoclastogenesis Involves Activation of Hyperpolarization-Activated Cyclic Nucleotide Modulated Channels via Changes in Membrane Potential

Abstract: Zinc is a trace element in the mammalian body, and increasing evidence shows its critical role in bone development and osteoclastogenesis. The relationships between zinc and voltage-gated ion channels have been reported; however, the effects of zinc on membrane potential and the related ion channels remain unknown. In this study, we found that zinc-induced hyperpolarization in RAW264.7 cells (RAW) was promoted by inhibition of hyperpolarization-activated cyclic nucleotide modulated channels (HCNs). In electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 39 publications
(93 reference statements)
0
26
0
Order By: Relevance
“…; Notomi et al . ). However, GFP fluorescence was too weak and indistinguishable from the autofluorescence signal.…”
Section: Resultsmentioning
confidence: 97%
“…; Notomi et al . ). However, GFP fluorescence was too weak and indistinguishable from the autofluorescence signal.…”
Section: Resultsmentioning
confidence: 97%
“…PI(3,5)P 2 inhibited osteoclastogenesis and depolarized the membrane potential. Previously, we have confirmed that membrane hyperpolarization promotes osteoclast differentiation (2). Thus, we tested our additional hypothesis, suggesting that membrane depolarization would affect osteoclastogenesis.…”
Section: Membrane Depolarization Inhibits Osteoclast Differentiationmentioning
confidence: 73%
“…(sRANKL, 50 ng/ml; Oriental Yeast, Tokyo, Japan). TRAP staining was performed as previously described (2,10). Ned19 (1 M; Tocris Bioscience, Bristol, UK), a TPC2 inhibitor, and YM201636 (100 nM; Tocris Bioscience), a PIKfyve inhibitor, were added to culture media in some experiments.…”
Section: Role Of Tpc2 In Osteoclastogenesis Under Low-mg 2؉ Conditionsmentioning
confidence: 99%
See 2 more Smart Citations